Perancangan dan Implementasi Sistem Pengelolaan Order Barang Berbasis Web dengan Laravel - Nabela Yulian Anggraini; Susanto Susanto (Jurnal Teknologi Informasi dan Multimedia, 2026)
CV. Surya Sarana Dinamika currently faces significant operational inefficiencies due to its man-ual, paper-based order management process. These challenges lead to frequent data recording errors, substantial delays in information flow, and a critical lack of real-time visibility regarding order status, which ultimately hinders effective administrative decision-making. This study aims to address these systemic issues by designing and implementing a web-based order management system utilizing the Laravel Framework. The system was developed using the Agile Development methodology, employing iterative cycles to ensure that the final product remains aligned with dynamic business requirements. The architecture is built upon the Model-View-Controller (MVC) pattern to ensure code scalability and long-term maintenance ease. Functional validation via Black-Box testing confirms that all core features, including order submission and purchasing validation, operate according to specifications. Quantitatively, the implementation resulted in a drastic efficiency increase; the average time for order submission decreased from 20-25 minutes to just 3-5 minutes (an efficiency gain of over 75%), while purchasing validation time was re-duced from 30-60 minutes to 5-10 minutes. These findings demonstrate that digital automation effectively eliminates manual bottlenecks and reduces the risk of human error. By providing cen-tralized data and real-time tracking, the system significantly enhances accountability and trans-parency within the company’s supply chain, providing a replicable model for digital transfor-mation in similar organizational contexts..